Optimization of Solid Lipid Microcapsule Matrix for Enhanced Release and Bioavailability of L-Lysine in Swine - Costanza Bonnici; Maria Federica Marchesi; Martina Felici; Federico Ghiselli; Roberta Majer; Benedetta Tugnoli; Guglielmo Gallina; Andrea Piva; Ester Grilli (Animals, 2025)
L-lysine (L-Lys) is the first-limiting amino acid in swine nutrition, but free-form supplements exhibit poor intestinal absorption, reducing their bioavailability. This study aimed to enhance the gastric retention, controlled intestinal release, and systemic availability of L-Lys by optimizing solid lipid microcapsules (SLMs). SLMs were formulated using hydrogenated triglycerides (C16:0 or C18:1), free fatty acids, and varying emulsifier concentrations. Gastric retention and intestinal release were evaluated in vitro under simulated gastrointestinal conditions (a pepsin buffer at pH 5.0 for 2 h, followed by a pancreatin buffer at pH 6.5 for up to 8 h at 39 °C). SLMs with hydrogenated triglycerides showed significantly higher gastric retention (94–95%) than those with free fatty acids (48%). Specifically, C16:0 triglyceride-based SLMs achieved 74% intestinal release, which was enhanced to 90% with 1% emulsifier. This refined formulation was subsequently evaluated in vivo using weaned pigs (three groups; n = 4) fed a basal cornmeal diet. The treatments included a single oral administration of saline solution (placebo), free L-Lys (0.17 g/kg BW), or L-Lys SLMs (0.38 g/kg BW, equally providing L-Lys at 0.17 g/kg BW). The SLMs delayed the L-Lys plasma peak (T. max. 3–4 h vs. 1 h) and significantly increased the total L-Lys amount in the plasma over 24 h, demonstrating the enhanced relative bioavailability of encapsulated L-Lys.